Challenges and Suggestions on Effective Functioning of Farmer Producer Companies by its Members in Shivamogga District of Karnataka - BM Dharmaraj; Beerannavar, Basavaraj; C Kavyashree; AT Krishnamurthy (Journal of Agricultural Extension Management, 2022)
The future of sustainable agriculture growth and food security in India depends on the performance of small and marginal farmers. However, these farmers are prone to challenges like lack of access to technology, forward linkage, market information etc. In India, different models of collectivization and institutional innovations have been employed to support small and marginal farmers. Farmer Producer Organization (FPO) is one such effort. Since 2002, around 7000 FPOs have been promoted by various agencies (MANAGE). Thus, considering the significance of FPOs, a study was conducted during 2019 to investigate the constraints faced by the members and their suggestions with respect to FPOs in Shivamogga. A total of 120 members from six FPOs were interviewed. The majority of the respondents expressed constraints such as problems related to lack of processing units non-existence of procurement system, absence of proper market linkage and poor credit facilities. The suggestions related to the establishment of processing units, conduct of awareness programmes about FPO, improvement of procurement system, enhancement of credit facility, need for proper market linkage, availability of CHS at lesser rates. This paper gives a detailed picture of challenges faced by the FPO members and their self-experienced feedback to improve their functionality.